Releases of brominated flame retardants (BFRs) from microplastics in aqueous medium: Kinetics and molecular-size dependence of diffusion - Sun, Bingbing; Hu, Yuanan; Cheng, Hefa; Tao, Shu (Water research (Oxford), 2019)
Microplastics (<5 mm) are increasingly detected in aquatic environment, and the high levels of brominated flame retardants (BFRs) contained in them can potentially impact water quality. This study characterized the release kinetics of polybrominated diphenyl ethers (PBDEs) and 1,2-bis(2,4,6-tribromophenoxy)ethane (BTBPE) from millimeter-sized microplastic pellets in water at environmentally relevant temperatures. Leaching rates of BFRs from the microplastic pellets made of acrylonitrile butadiene styrene (ABS) were found to be controlled by their diffusion within the plastic matrix, and their diffusion coefficients (D) in the plastic matrices ranged from 10−28.30 to 10−20.84 m2 s−1. The apparent activation energies of the BFRs’ diffusion coefficients were estimated to be in the range of 64.1–131.8 kJ mol−1 based on their temperature dependence and the Arrhenius equation. The diffusion coefficients of the BFRs decrease with their molecular diameters, while the activation energies for diffusion increase with the molecular diameters, which are indicative of significant steric hindrance for BFR diffusion within the plastic matrices. A semi-empirical linear relationship was observed between Log10D and the glass transition temperature (Tg) of plastics, which allows prediction of the diffusion coefficients of BFRs in other types of microplastics commonly found in marine environment. The half-lives of BFR leaching (i.e., 50% depletion) from the microplastic pellets would range from tens of thousands to hundreds of billions of years at ambient temperatures if their physical and chemical structures could remain intact. Although the release fluxes of BFRs from microplastics are extremely low under the model conditions, a range of physical and chemical processes in the natural environment and the digestive systems of organisms that ingested them could potentially accelerate their leaching by causing breakdown and swelling of the plastic matrices. [Display omitted] •Leaching rates of BFRs were controlled by diffusion within the plastic matrix.•The diffusion coefficients of BFRs in ABS ranged from 10−28.30 to 10−20.84 m2 s−1•The activation energies for diffusion of BFRs ranged from 64.1 to 131.8 kJ mol−1•Diffusion coefficients of BFRs in plastic matrix depend on their molecular sizes.•Diffusion coefficients show dependence on the plastic's glass transition temperature.